Ocena oraz porównanie zachowań żywieniowych u osób uprawiających sport zawodowo i amatorsko = Evaluation and comparison of nutritional behavior of people practicing professional and amateur sport - Kałużny, Krystian; Śpica, Dorota; Drobik, Przemysław; Michalska, Anna; Kałużna, Anna; Kochański, Bartosz; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kałużny Krystian, Śpica Dorota, Drobik Przemysław, Michalska Anna, Kałużna Anna, Kochański Bartosz, Zukow Walery. Ocena oraz porównanie zachowań żywieniowych u osób uprawiających sport zawodowo i amatorsko = Evaluation and comparison of nutritional behavior of people practicing professional and amateur sport. Journal of Education, Health and Sport. 2016;6(2):301-310. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46813 http://ojs.ukw.edu.pl/index.php/johs/article/view/3408 https://pbn.nauka.gov.pl/works/717687 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. OCENA ORAZ PORÓWNANIE ZACHOWAŃ ŻYWIENIOWYCH U OSÓB UPRAWIAJĄCYCH SPORT ZAWODOWO I AMATORSKO EVALUATION AND COMPARISON OF NUTRITIONAL BEHAVIOR OF PEOPLE PRACTICING PROFESSIONAL AND AMATEUR SPORT Krystian Kałużny1, Dorota Śpica2,3, Przemysław Drobik3, Anna Michalska3,4, Anna Kałużna1,5, Bartosz Kochański1, Walery Zukow6 1 Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2 Zakład Higieny i Epidemiologii, Katedra Higieny, Epidemiologii i Ergonomii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3 Bydgoska Szkoła Wyższa w Bydgoszczy 4 Zakład Nauk Społecznych, Katedra Marketingu i Rozwoju Regionalnego, Wydział Zarządzania, Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckich w Bydgoszczy 5 Katedra Chorób Naczyń i Chorób Wewnętrznych, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 6 Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Wstęp. Regularna aktywność fizyczna i liczne obciążenia, jakim poddawani są sportowcy przy nieodpowiednio dobranej diecie może powodować niedobory pokarmowe. Jakościowe i ilościowe nieprawidłowości żywienia i zachowań żywieniowych mogą wpływać na spadek zdolności motorycznych, obniżenie koncentracji, zaburzenie procesów regeneracyjnych oraz większą podatność na przemęczenie i przeciążenia organizmu sportowca. Cel pracy. Celem pracy jest ocena oraz porównanie zachowań żywieniowych u osób uprawiających sport zawodowo i amatorsko. Materiał i metody. Badania przeprowadzono na grupie 100 osób, w tym 50 osób uprawiających sport zawodowo (zrzeszonych i reprezentujących kluby sportowe) oraz 50 uprawiających sport amatorsko. Ocenę zachowań żywieniowych dokonano z wykorzystaniem autorskiej ankiety. Wyniki. Z analizy przeprowadzonych badań wynika, że znaczny odsetek osób uprawiających sport zawodowo i amatorsko nie przestrzega zaleceń dotyczących liczby i pory spożywania posiłków. W obu grupach występowały nieprawidłowości w nawadnianiu, zarówno w ciągu dnia, jak również przed, w trakcie i po treningu. Z badań wynika, że regularne spożywanie napojów energetycznych deklaruje 81% zawodowców oraz 75% amatorów. Spożywanie alkoholu kilka razy w tygodniu zaobserwowano u 35% zawodowców oraz 67% amatorów sportu. Grupa zawodowców istotnie statystycznie częściej spożywała posiłki najpóźniej do 2h przed snem, częściej uzupełniała płyny wodą mineralną oraz spożywała mniej alkoholu niż grupa amatorów. Wnioski. 1. Zachowania żywieniowe u osób uprawiających sport zawodowo i amatorsko są nieprawidłowe. 2. Częstość występowania prawidłowych zachowań żywieniowych wśród osób uprawiających sport zawodowo i amatorsko jest na zbliżonym poziomie. Abstract Introduction. Regular physical activity and frequent load in athletes with inappropriately chosen diet can cause nutritional deficiencies. Qualitative and quantitative irregularities of nutrition and nutritional behaviors could affect motor skills, decrease in concentration, impaired regenerative processes and greater susceptibility to fatigue and overload the athlete's body. Aim of the study. The aim of the study was to evaluate and compare the nutritional behaviors of people practicing professional and amateur sport. Material and methods. The study was conducted on a group of 100 people, including 50 people practicing sport professionally (affiliated and representing sports clubs) and 50 amateur athletes. Assessment of nutritional behaviors were made using a proprietary questionnaire. Results. The analysis of the study shows that a significant percentage of people practicing sport professionally and amateur does not follow the recommendations concerning the number and timing of food ingestion. In both groups there were irregularities in the irrigation, both during the day as well as before, during and after exercise. Research shows that regular consumption of energy drinks declares 81% professionals and 75% amateurs. Consumption of alcohol several times a week was observed in 35% of professionals and 67% of amateur sport. Group professionals significantly more often ate meals no later than 2 hours before bedtime, often replenish fluids mineral water and consumed less alcohol than a group of amateurs. Conclusions. 1. Nutritional habits of people practicing sports professionals and amateurs are incorrect. 2. The incidence of normal nutritional behaviors among athletes professional and amateur is at a similar level. Słowa kluczowe: zachowania żywieniowe, sport. Keywords: dietary behaviours, sport.